การสร้างอัตลักษณ์ของตัวละครผู้อพยพในนวนิยายเรื่อง Jacob beschließt zu lieben (เมื่อยาคอบตัดสินใจที่จะรัก) และ Der Mann, der das Glück bringt (บุรุษผู้มาพร้อมความสุข) ของคาตาลิน โดเรียน ฟลอเรสคู (Catalin Dorian Florescu) - อารตี แก้วสัมฤทธิ์ (กองบรรณาธิการวารสารอักษรศาสตร์, 2022)
This research article outlinesthe process of identity formation of migrant characters in the novels Jacob beschließt zu lieben(2011) and Der Mann, der das Glück bringt(2016) byCatalin Dorian Florescu, afamouscontemporary Swiss author who was born in Romania.The study shows that the characters in both novels form their identities in similar ways.Due to hard social contexts and their longings for survival, they form flexible and fluid identities which donot adhere to their ethnic and cultural roots.Such identity formation which crossescultural boundaries,and the settings in places of cultural hybridity like Banat and New York, moreover, reflectthe illusion of an essential, fixed and permanent identity and the assumption that a nation is composed of a single"pure" culture.